Palliative medicine education—Bed Race, The End of Life Board Game in undergraduates. Issue 4 (17th September 2021) - Harris, Dylan G; Atkinson, Clea
Abstract : Background: Educational board games facilitate active learning to conceptualise knowledge, and, promote collaborative learning and team work. Despite increasing interest in them, use in palliative and end of life care has been very limited to date. Method: In 'Bed race, The End of Life Game', participants are divided into four teams who move a model hospital bed around a board to collect items (syringe driver; Do Not Attempt Resuscitation form; oral hydration gel; a 'heart'; Just In Case medicines). To obtain items at themed 'checkpoints', each team needs to answer quiz questions, which require application of clinical knowledge and/or communication skills. Pregame and postgame quiz scores and feedback were collected from 12 game sessions involving 251 year 5 medical students. Results: 169 (67%) of students completed pregame and postgame anonymous quiz questions and free-text feedback. Postgame quiz scores were higher for each topic, and the difference in the paired pregame and postgame questionnaires was statistically significant (p<0.05). Themes from the free-text feedback included 'engaging and fun'; 'relevant learning'; 'peer learning and team work'. Conclusions: Educational board games are not a new panacea for education, but the concept can be successfully applied in palliative care.